Pengaruh Keterampilan Variasi Mengajar Guru dan Minat Belajar terhadap Aktivitas Belajar Siswa pada Mata Pelajaran IPS Terpadu - Asriyati Ikhsan; Frahmawati Bumulo; Abdulrahim Maruwae; Roy Hasiru; Maya Novrita Dama (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to determine the influence of teachers‘ teaching variation skills and learning interest on student’ learning activities, both partially and simultaneously, in the subject of Social Science for class VIII at SMP Negeri 1 Atinggola. The study adopted a quantitative approach utilizing a correlational method. The Primary data were obtained through questionnaire. The sample of the study consisted of 64 respondents. Furthermore, the data was performed using multiple linear regression. The findings indicate that both teaching variation skliss and learning interest significantly influence students’ both patially and simultaneously. The partial influence of the teaching variation variable on learning activities is 29.6%, whereas the partial influence of learning interest on learning activities is 27,9%. The simultaneous influence of teaching variation and learning interest on learning activities is 57,5%, with the remaining 42.5% influenced by other unexamined variables.